Genomic Analysis of Salmonella enterica Serovar Typhimurium Characterizes Strain Diversity for Recent U.S. Salmonellosis Cases and Identifies Mutations Linked to Loss of Fitness under Nitrosative and Oxidative Stress - Hillary S. Hayden (American Society for Microbiology, 2016)
ABSTRACT Salmonella enterica serovar Typhimurium is one of the most common S. enterica serovars associated with U.S. foodborne outbreaks. S. Typhimurium bacteria isolated from humans exhibit wide-ranging virulence phenotypes in inbred mice, leading to speculation that some strains are more virulent in nature. However, it is unclear whether increased virulence in humans is related to organism characteristics or initial treatment failure due to antibiotic resistance. Strain diversity and genetic factors contributing to differential human pathogenicity remain poorly understood. We reconstructed phylogeny, resolved genetic population structure, determined gene content and nucleotide variants, and conducted targeted phenotyping assays for S. Typhimurium strains collected between 1946 and 2012 from humans and animals in the United States and abroad. Strains from recent U.S. salmonellosis cases were associated with five S. Typhimurium lineages distributed within three phylogenetic clades, which are not restricted by geography, year of acquisition, or host. Notably, two U.S. strains and four Mexican strains are more closely related to strains associated with human immunodeficiency virus (HIV)-infected individuals in sub-Saharan Africa than to other North American strains. Phenotyping studies linked variants specific to these strains in hmpA and katE to loss of fitness under nitrosative and oxidative stress, respectively. These results suggest that U.S. salmonellosis is caused by diverse S. Typhimurium strains circulating worldwide. One lineage has mutations in genes affecting fitness related to innate immune system strategies for fighting pathogens and may be adapting to immunocompromised humans by a reduction in virulence capability, possibly due to a lack of selection for its maintenance as a result of the worldwide HIV epidemic. IMPORTANCE Nontyphoidal Salmonella bacteria cause an estimated 1.2 million illnesses annually in the United States, 80 million globally, due to ingestion of contaminated food or water. Salmonella Typhimurium is one of the most common serovars associated with foodborne illness, causing self-limiting gastroenteritis and, in approximately 5% of infected patients, systemic infection. Although some S. Typhimurium strains are speculated to be more virulent than others, it is unknown how strain diversity and genetic factors contribute to differential human pathogenicity. Ours is the first study to examine the diversity of S. Typhimurium associated with recent cases of U.S. salmonellosis and to provide some initial correlation between observed genotypes and phenotypes. Definition of specific S. Typhimurium lineages based on such phenotype/genotype correlations may identify strains with greater capability of associating with specific food sources, allowing outbreaks to be more quickly identified. Additionally, defining simple correlates of pathogenesis may have predictive value for patient outcome.